EFFECT OF STRATEGIC MINERAL MIXTURE ON THE PERFORMANCES OF SOW AND PIGLETS (Indian Journal of Animal Production and Management, 2013)
An experiment was carried out to see the effect of specific minerals on performances of sow as well as piglets. A total of 10 pure bred Hampshire sows of first or second farrowing were randomly selected and placed under Experimental Group. Another 10 sows of the same breed and reproductive status served as Control. The animals were kept under intensive system in 30 sow unit, College of Veterinary Science, AAU, Guwahati. Animals were offered concentrate mixture two times a day – morning and evening. Sows under experimental group were supplemented with strategic mineral mixture (AAUVETMIN) while Control animals were supplemented commercial mineral mixture. The mean litter size at birth in experimental and control group were 9.90 ± 0.67 and 8.90 ± 0.90 respectively. Mean litter size at weaning was recorded, respectively as 8.70 ± 0.75 and 7.60 ± 0.54 in experimental and control group. The mean litter weight and average individual body weight of piglets at birth and weaning in experimental group were 14.50 ± 1.01 & 85.62 ± 7.06 and 1.48 ± 0.04 & 9.88 ± 0.12 kg while in control group respective values were 12.77 ± 1.14 & 67.80 ± 5.92 and 1.46 ± 0.04 & 8.87 ± 0.41 kg. The ratio of male to female piglets at birth in experimental and control groups were 1 : 1.09 and 1 : 1.41. The corresponding values for male to female ratio at weaning were 1 : 1.18 and 1 : 1.24. The numbers of female piglets were higher than male in both experimental and control groups. In experimental group survivability rate from birth to weaning was recorded as 87.88% against 85.39% in control group. The supplementation of strategic mineral mixture to the sows during pregnancy could increase the survivability rate by 2.49%.
Keywords: Mineral mixture; sow; litter size; litter weight; survival rate